A Delivery Note - Zha, Zed (Ars Medica, 2023)
In medicine, we write notes in the driest language, drained of all emotions, especially during a procedure. As a family doctor, I form meaningful bonds with patients, especially with those whom I have cared for for nine months during their pregancies. And when I finally deliver their babies, it's an emotional journey for the patients and myself. In this essay, I dissect what really happens during a "NSVD", normal spontanous vaginal delivery.